Sistem Informasi Tunggakan Rekening Air pada PDAM Tirta Mon Krueng Baro - Hermansyah; Iqbal, Taufiq; Ismail (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Customer data management and payment arrears are critical aspects of the operations at PDAM Tirta Mon Krueng Baro. However, the manual recording methods still in use often lead to issues such as inaccurate data, slow administrative processes, and difficulties in tracking customer payment statuses. To address these challenges, the Water Bill Arrears Information System was developed to facilitate integrated and efficient data management. This system utilizes Microsoft Visual Basic 6.0 for the interface and Microsoft Access 2007 as the database platform. The system development involved several stages, including requirements analysis, database design, and user interface creation. One of the key features of the system is its ability to record, process, and display customer data and arrears in real time. It also includes a reporting module, enabling administrators to generate summaries of arrears and payments quickly and accurately. The implementation of this system has improved operational efficiency, minimized data entry errors, and expedited decision-making regarding payment and arrears management. Results indicate that the system outperforms the manual method in managing data, providing users with easier access to track arrears and generate reports for decision-making. Consequently, this system serves as a practical solution for enhancing the quality of service and management at PDAM.